Comparison of Two Multidisciplinary Occupational Rehabilitation Programs Based on Multimodal Cognitive Behavior Therapy on Self-Rated Health and Work Ability - Lyby, Peter Solvoll; Johansen, Thomas; Aslaksen, Per M. (Frontiers in Psychology, 2021)
Objective: Musculoskeletal pain and common mental disorders constitute the largest proportion of people who are on sick leave. This study investigated the efficacy of two multidisciplinary occupational rehabilitation programs on self-rated health and work-related outcomes. The interventions were identical in content but differed in length. It was hypothesized that a longer inpatient program would yield greater improvements than a shorter outpatient program. Methods: Patients were sick-listed workers referred to occupational rehabilitation by the Norwegian Labor and Welfare Administration. A non-randomized 2 Condition (20 days, n = 64 versus 12 days, n = 62) × 4 repeated measures (start, end, 3 months, 12 months) between-subject design was used. Both programs were based on multimodal cognitive behavior therapy with a return-to-work focus. Health-related questionnaires were the Subjective Health Complaints inventory, Hospital Anxiety and Depression Scale, and SF-36 Bodily Pain. Work-related questionnaires were the Work Ability Index, the Fear-Avoidance Beliefs Questionnaire, Return To Work Self-Efficacy, and Return To Work expectations. Intervention effects were estimated using linear mixed models and Cohen’s d. Results: The results revealed that both groups improved on the selected outcomes. Within-group contrasts and effect sizes showed that the inpatient group showed larger effect sizes at the end of rehabilitation and 12 months post-intervention for work-related outcomes than the outpatient group. Conclusion: Both programs were efficacious in improving health- and work-related outcomes during and after rehabilitation, but the inpatient group generally displayed stronger and more rapid improvements and was more stable at one-year postintervention.